Sistem Pendukung Keputusan Rekomendasi Pembelian Motor Pada Dealer Dinamika Honda menggunakan Metode Analytics Hierarchy Process (Yayasan Kawanad, 2023)
Motor vehicles, particularly motorcycles, have become an integral part of daily life in many countries. Selecting a motorcycle that meets the user's needs is a critical decision. This study employs the Analytical Hierarchy Process (AHP) method to aid the decision-making process in selecting Honda motorcycles. The AHP method is utilized to describe and measure various relevant criteria in motorcycle selection, such as fuel efficiency, performance, design, price, and safety factors. Subsequently, the sub-criteria and relative weights of each criterion are determined through the participation of an expert panel consisting of motorcycle users, automotive mechanics, and transportation safety experts. The data is analyzed using AHP software, and the results prioritize each type of Honda motorcycle based on the defined criteria and sub-criteria. The recommendations for selecting Honda motorcycles are then compiled based on the rankings provided by the AHP method. The results of research members of the picture of important factors in the selection of Honda motorcycles, as well as providing a systematic and structured approach to the Motorika Consumers Candidates to Bur in Motorsumen Moolensumen Buyers.